1995
DOI: 10.1079/bjn19950064
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between smoking and antioxidant nutrient status

Abstract: The present study was designed to investigate the relationship between smoking and antioxidant nutrient intake and status. Smoker (n 44) and non-smoker (n 44) male students attending Dhaka University, aged between 22 and 28 years and Living in a University Hall of Residence, were selected for the present study. Mean age, body weight, BMI and blood pressure were similar for both the smokers and non-smokers. Mean energy, protein and fat intakes were similar for both groups. Smokers had lower intakes of dietary v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
2
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(41 citation statements)
references
References 24 publications
4
34
2
1
Order By: Relevance
“…Our results highlighted smoking and education as other significant determinants of serum zinc levels only in women. The higher serum zinc concentration in heavy female smokers compared with never and former smokers was unexpected although this observation was in agreement with some previous reports (Dubick and Keen, 1991;Faruque et al, 1995;Kim et al, 2003). Education is the most commonly used measure of socioeconomic status in epidemiological studies (Winkleby et al, 1992) and our results evidenced a serum zinc decreased with increased education.…”
Section: Discussionsupporting
confidence: 82%
“…Our results highlighted smoking and education as other significant determinants of serum zinc levels only in women. The higher serum zinc concentration in heavy female smokers compared with never and former smokers was unexpected although this observation was in agreement with some previous reports (Dubick and Keen, 1991;Faruque et al, 1995;Kim et al, 2003). Education is the most commonly used measure of socioeconomic status in epidemiological studies (Winkleby et al, 1992) and our results evidenced a serum zinc decreased with increased education.…”
Section: Discussionsupporting
confidence: 82%
“…However, the results do not correspond to those of Faruque, et al 52 who reported a non significant difference in the dietary protein and fat intake between smokers and non-smokers. Similarly, no significant difference in the mean dietary vitamin A intake between smokers and non-smokers suggest that smoking did not have any significant affect on the dietary vitamin A intake of smokers.…”
Section: 13contrasting
confidence: 56%
“…In addition, geographical location seems to be an important factor in determining blood levels of some trace elements because the levels can be linked to the influences of geochemistry on soils, food, and water supply (8,(16)(17)(18)(19). Finally, social and environmental conditions and lifestyle such as tobacco consumption are also factors influencing the trace element status (16,(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%